Guardianship council and electoral policy: the formation of the party career from the role of guardianship adviser (Research, Society and Development, 2022)
The article deals with the formation of the party’s political career from the exercise of the public function of tutelary councilor. This analytical overview was inscribed from two case studies, which took place at the Guardianship Council (CT) in the municipality of Horizonte, State of Ceará. In theory, this social space – Guardianship Council – creates “bridges” for the party’s political career, allowing outsiders to gain public visibility that, without this resource, it would not be possible to enter the party’s political space. Thus, for this reflection, we bring the trajectories of two citizens called “ordinary” by civil society, who entered the tutelary space and from there climbed their party political career working the elements contained in the tutelary field. Direct observation and interviews were the methodologies used for the empirical survey. The article concludes that, through tactics put into practice by any citizen who enters the tutelary space, the way this institutional space is designed favors the formation of political party careers.